Manufacturing of Vortex Granulators: Simulation of the Vortex Fluidized Bed Functioning under the Disperse Phase Interaction in the Constrained Motion - Artyukhov, Artem; Krmela, Jan; Krmelová, Vladimíra (Manufacturing Technology Journal, 2020)
The work presents the computer simulation results describing the motion of the interacting particles in a vortex fluidized bed (the constrained motion). The data obtained reveal the peculiar features of the polydisperse system motion in the apparatuses with the variable cross-section of the workspace. The empirical coefficient determining the residence time of a particle in the vortex fluidized bed was calculated. An algorithm of the residence time cal-culations for a particle in the vortex fluidized bed under the constrained motion is developed. The results of com-puter simulation were a part of engineering (technological and constructive) algorithm of calculation for the fu-ture manufacturing of granulator?s industrial sample.
Keywords: Computer Modeling; Vortex Granulator; Constrained Motion; Optimization